1997
DOI: 10.1097/00007890-199710150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Donor Alloantigens in Antiadhesion Therapy Induces Antigen-Specific Unresponsiveness to Islet Allografts1,2

Abstract: These results indicate that anti-LFA-1 mAb treatment prevents T-cell activation leading to rejection, but results in a T-cell receptor engagement leading to antigen-specific unresponsiveness maintained by transferrable suppressor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The Ag-unresponsive T cells have been shown to be a tool for Ag-specific adoptive immunotherapy in transplant medicine (2,3). In this study we observed that adoptive transfer of anti-B7-treated T cells increased fetal viability, whereas adoptive transfer of anti-B7-treated B cells did not.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The Ag-unresponsive T cells have been shown to be a tool for Ag-specific adoptive immunotherapy in transplant medicine (2,3). In this study we observed that adoptive transfer of anti-B7-treated T cells increased fetal viability, whereas adoptive transfer of anti-B7-treated B cells did not.…”
Section: Discussionmentioning
confidence: 47%
“…Thus, induction of maternal immunosuppression to the embryo/fetus is a main concern for maintaining materno-fetal tolerance. In organ transplantation, it has been shown that anergic T cells generated by blocking costimulatory pathway can be transferred as suppresser cells to prevent allograft rejection (2,3). However, to our knowledge, the regulatory role of these T cells treated with anti-B7-1/B7-2 mAbs for suppressing maternal immune responses to the allogeneic fetus in vivo has not been investigated previously.…”
mentioning
confidence: 99%
“…In the present study, a high systemic production of an immunoadhesin, using Ad-mediated in vivo transfer of the gene encoding sICAM-1/Ig, interfered with the LFA-1-ICAM-1 pathway and significantly prolonged islet allograft survival in mice. Monoclonal antibodies directed against ICAM-1 (Zeng et al, 1994;Katz et al, 2000), LFA-1 (Nishihara et al, 1997;Katz et al, 2000;Nicolls et al, 2000), or both (Grochowiecki et al, 2000;Katz et al, 2000) as well as ICAM-1 antisense oligonucleotides (Katz et al, 2000) have already been used in multiple animal models. According to these data, anti-LFA-1 MAb-specific tolerance has been reported using short-term administration of anti-LFA-1 MAb, confirming the critical role of the LFA-1-ICAM-1 pathway in allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The LFA-1-ICAM-1 interaction plays an essential role in the adhesion of leukocytes to endothelial cells, and is an important costimulatory signal in immunocompetent cells (Springer, 1994). Administration of anti-ICAM-1 and/or anti-LFA-1 monoclonal antibodies (MAbs) has been used in various allo-or xenograft rodent models such as heart (Isobe et al, 1992), islet (Gotoh et al, 1994;Zeng et al, 1994;Nishihara et al, 1997;Katz et al, 2000;Nicolls et al, 2000), small bowel (Sarnacki et al, 2000), pancreas (Kawabe et al, 1996), and liver transplantation (Harihara et al, 1996). Studies of humans confirmed that anti-ICAM-1 or anti-LFA-1 antibodies can significantly prolong kidney or bone marrow graft survival (Fischer et al, 1991;Haug et al, 1993;Hourmant et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Isobe et al (5) demonstrated that transient-combined treatment with Abs directed against both LFA-1 and its ligand ICAM-1 triggered profound prolongation and tolerance to cardiac allografts. Other studies since have demonstrated the efficacy of anti-LFA-1 and/or anti-ICAM-1 therapy in experimental and clinical transplantation of islets (6,7), kidney (8,9), bowel (10,11), liver (12,13), bone marrow (14,15), and heart (15)(16)(17).…”
mentioning
confidence: 99%